A passive wireless tracking system for indoor assistive monitoring - Hee Kho, Yau; Soon Chong, Nguan; Caglar Kizilirmak, Refik (IEEE Computer Society, 2016)
This paper presents a design concept and implementation of an indoor passive tracking system that utilises an array of Wi-Fi transceivers, and without any electronic device or tag attached to the object being tracked. Such tracking is made possible by exploiting the fundamental characteristic of signal attenuation due to object blocking, i.e. shadowing, that is prevalent in a typical wireless communication system.
Keywords: indoor positioning; object tracking; radio frequency; received signal strength; wireless communications; Research Subject Categories::TECHNOLOGY::Engineering physics